The Impact of Workload on the Performance of SMPN Teachers in South Blitar Regency with Compensation as a Moderation Variable - Dikhy Candra Putra; Bambang Septiawan (International Journal of Sustainable Applied Sciences, 2024)
This research brings out a purpose to determine the impact of workload on performance and compensation. In addition to teaching, teachers have additional tasks that can be a workload but it can encourage teacher competence in carrying out their duties at school. The type of research conducted by the author includes quantitative research using a Cause-and-Effect Approach. In this research, the population was all teachers at UPT SMP Negeri 1 Sutojayan, UPT SMP Negeri 1 Binangun, and UPT SMP Negeri 2 Sutojayan. The results showed that workload affects teacher performance, this is indicated by workload (X), which has a calculated t-value of 5.94 and a significance value of 0.00. Workload x Compensation (Z) has a calculated t value of 7.51 and a significance value of 0.00. In t count (7.51) > t table (1.67) and significance (0.00) < (0.05) so that H0 is rejected and Ha is accepted, this implies that compensation can moderate the workload positively and significantly to teacher performance.